Peningkatan Produktivitas Konstruksi Melalui Pemilihan Metode Konstruksi - Nugroho, Paulus Setyo (Jenderal Soedirman University, 2012)
Productivity growth in the construction is lower than that of in the industry sector. Level of innovation in this sector is too low. Many problems of inefficiency in the construction process are a lotof waste of resources that do not produce value. According to Â LCI (Lean ConstructionInstitute) waste in the construction industry is about 57% while the activity that adds value is only 10%. The construction industry has a lot to learn from manufacture industry. Some innovations by applying an appropriate and efficient Â methods in the field of construction adopted many of the manufacturing, including modular systems/fabrication (precast concrete). Construction materials are mass produced in acontrolled environment and then assembled inthe site. The use of precast on any project shows that there are advantages obtained are: cheaper, faster/more productive and guaranteed quality. The duration of the Rusunawa (Simple Flats for Rent) Structure construction phase in Cilacap for precast method is 168 days while for the implementation of the conventional method is 196 days. The duration of the construction of precast structures is faster 28 days (14%) faster than that of the conventional structures. In high-speed rail project on the border of Belgium and the Netherlands, use Rheda 2000 NL method, which development of Rheda method, can increase productivity and lower overtime costs as 24.6%. In the residential case, quicklyconstructed building criteria can be categorizedinto several aspects, such as dimensions, weight components and connection systems.The suitable selection criteria will accelerate instalment proses of the wall panel.